Implementasi Metode Permainan Bahasa Grammatical Hunting dalam Pembelajaran Bahasa Arab di Kelas 3/1 Mutawasith Khoiriyah Wittaya Mulnithi Betong, Yala, Thailand Tahun Ajaran 2019/2020 - Zaimatuz Zakiyah; Nurul Huda (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
Abstract: As one component of language learning, the learning method becomes a determinant of the course of an effective and efficient learning process. This requires the professionalism of teachers to be able to implement certain methods in the learning process. The purpose of this paper is to determine the application of the Grammatical Hunting language game method, to find out students' responses to the learning methods applied, and their advantages and disadvantages in learning Arabic in class 3/1 Mutawasith Khoiriyah Wittaya Mulnithi Betong, Yala, Thailand. This research is a descriptive quantitative research. The sample of this research is students of class 3/1 Mutawasith Khoiriyah Wittaya Mulnithi Betong, Yala, Thailand was 25 students. The research technique applied was a non-test technique with data collection instruments in the form of observation, interviews, questionnaires, and documentation. The results showed that (1) The application of the Grammatical Hunting language game method consisted of 3 stages, namely: introduction, core activities, and closing. (2) Students show the best responses to the methods applied in the form of increased interest and activeness in learning Arabic, that is 89,77 %. (3) The advantages of this method are eliminating boredom, creating cooperation, and supportive between students, while the disadvantages of applying this method, namely the number of groups and the crowded class.